Bahasa Inggris Bahasa Inggris - Aurum Azzahra; Badrus Zaman; Heru Susanto (Jurnal Penelitian Pendidikan IPA, 2025)
As a developing wastewater treatment system, constructed wetlands have increasingly been implemented in several regions due to their high purification efficiency and relatively low operational costs. This study aims to improve the quality of treated water from domestic Wastewater Treatment Plants (WWTP) through natural filtration methods based on sandy soil media that contain 70% soil and 30% sand and planted with Heliconia psittacorum and Napier grass (Pennisetum purpureum). The natural filtration such as constructed wetland were applied in open tanks, with varying retention times 2, 4, 6, 8 and 10 days to test treatment effectiveness, the wastewater quality was analyzed based on parameters including COD, BOD, TSS, ammonia, phosphate, nitrate, and pH. The results showed a significant reduction in pollutant concentrations, with the highest removal efficiency reaching for BOD 86.41%, COD at 86.54%, nitrate at 98.92%, phosphate at 97.86%, at 99.84% and TSS at 86.39% resulting in treated water that meets the domestic wastewater quality standards according to Government Regulation No. 22 of 2021 for class 3., enhancing nutrient uptake and supporting microbial activity within the filtration media. This method offers a cost-effective, environmentally friendly alternative for domestic wastewater treatment, suitable for application in areas with limited land availability and aiming for sustainable water management.